Diversity of Bivalve Species in the Intertidal Zone of Lande Beach, Motion Makmur Village, Sampolawa Sub-District - Lusiana Lusiana; Agus Slamet; Kusrini Kusrini (P3M IAI Nusantara Batang Hari, 2024)
This study aims to determine the types of bivalves in the intertidal zone of Lande Beach, Gerak Makmur Village. This research is classified as quantitative descriptive research using the search method. The research has 3 stages, namely the observation stage, the sampling stage at the research location, and the identification stage. The data obtained were then analyzed descriptively including body shape, color, pattern and body size. Based on the results of research conducted in the intertidal zone of Lande Beach, Gerak Makmur Village, Sampolawa District, 7 families and 8 species of bivalves were found, namely Fragumunedo, Tridacnacrocea, Tranchycardium rogusum, Spondylus versicolor, Pinctada maxima, Anandara gubernaculum, and Atrinavexillum. Keywords: Diversity, Intertidal, Sampolawa